Aprendizagem pela Internet na formação docente continuada para a gestão da violência na escola - Castro, Janiery da Silva (2013)
Considering the acquisition of knowledge as something that occurs throughout life, the present dissertation investigates the role of internet learning in teachers (planned or unplanned) continuing learning for the management of school violence. It does so to find out if knowledge acquired through internet helps teachers manage violence at school and, if so, how it helps. To answer these questions, we analyze the knowledge acquired by four public school teachers in the city of João Pessoa. They all participated in the program "Escola que Protege" during the year 2010. The research method was qualitative and the data were collected through semi-structured interviews. They were totally transcribed and analyzed from the perspective of discourse analysis (BARDIN, 1977) and in the light of the literature on computer-mediated education (PRIMO, 2003; LÉVY, 2007; LITTO; FORMIGA. 2009; CASTELLSs, 2010, etc.). We raised categories which allowed us to describe pedagogical practices and teachers continuous learning. The results show that the teachers use the internet almost daily, to socialize, to search for information, to plan lessons, and that knowledge is acquired through the use of the network. The participants consider computer mediated interaction necessary for their work, which requires constant study. The internet is used for different reasons, but its use is not necessarily directed to the acquisition of strategies to manage school violence; the participants see school violence as an outcome of their home education. This argument brought us to the understanding that participants are not strongly motivated to intervene and to manage conflicts and to learn strategies to tackle these phenomena. As a consequence of these findings, we recommend that teachers use the internet as a tool to interact, to find and to provide support by creating: virtual free instruments for continuing learning such as blogs, social networks and virtual forums, sites in which scientific and pedagogical information can be found, and spaces for the exchange of ideas. By doing so they would contribute to the increase of the knowledge and to the improvement of the training in school conflict management, even beyond their professional world. We also believe that it is possible and necessary to develop some social skills (especially those related to distant interaction and communication) that can give support to teachers in the task of teaching how to live in society.